Chipmunks - Switzer, Merebeth; Kelsey, Elin. (New York : Scholastic, 1996)
Describes the physical characteristics, habits, and habitats of chipmunks and beavers.
Includes indexes.
Two books bound back to back.
Keywords: Chipmunks -- Juvenile literature; Beavers -- Juvenile literature